Association of diet quality and mental wellbeing among Universiti Sains Malaysia undergraduate medical students - Rozmi, Siti Najihah (Universiti Sains Malaysia, 2024)
Emerging evidence suggests that diet quality profoundly impacts mental health, linking poor dietary habits to increased risks of depression, anxiety, and stress. This study explored associations between diet quality and mental well-being among Universiti Sains Malaysia undergraduate medical students. A cross-sectional study was conducted with 139 participants, using the Depression, Anxiety, and Stress Scale (DASS-21) for mental health assessment and the Standardized Malaysian Healthy Eating Index (SM-HEI) for diet quality. Spearman Rho correlation tested relationships between variables. No significant correlations were found between diet quality and mental well-being (p=0.780, r=0.322). Findings indicated most students experienced normal to mild levels of depression, anxiety, and stress Specifically, 62.0% (n=18) of males reported normal levels of depression 24.0% experiencing moderate to severe depression ,58.6% (n=17) reported normal stress levels and 55.1% experiencing moderate to severe anxiety. In contrast, among females, 65.5% (n=72) reported normal levels of depression, 17.3% moderate to severe depression ,45.5% experiencing moderate to severe anxiety and 78.2% (n=86) reported normal stress level. This shows female student has better diet quality. In terms of diet quality, the study found that no participants had a high-quality diet. Most female students (60%, n=72) had a moderate-quality diet compared to only 5% (n=6) of males, while 18.3% (n=22) of females and 4.2% (n=20) of males had a low-quality diet, showing females had better diet quality. No significant correlations were found between diet quality and mental well-being (p=0.780, r=0.322). These results suggest that factors beyond diet quality contribute to mental well-being.